Is genotyping of single isolates sufficient for population structure analysis of Pseudomonas aeruginosa in cystic fibrosis airways? - Sommer, Lea M. (2016)
The primary cause of morbidity and mortality in cystic fibrosis (CF) patients is lung infection by Pseudomonas aeruginosa. Therefore much work has been done to understand the adaptation and evolution of P. aeruginosa in the CF lung. However, many of these studies have focused on longitudinally collected single isolates, and only few have included cross-sectional analyses of entire P. aeruginosa populations in sputum samples. To date only few studies have used the approach of metagenomic analysis for the purpose of investigating P. aeruginosa populations in CF airways. Results: We analysed five metagenomes together with longitudinally collected single isolates from four recently chronically infected CF patients. With this approach we were able to link the clone type and the majority of SNP profiles of the single isolates to that of the metagenome(s) for each individual patient. Conclusion: Based on our analysis we find that when having access to comprehensive collections of longitudinal single isolates it is possible to rediscover the genotypes of the single isolates in the metagenomic samples. This suggests that information gained from genome sequencing of comprehensive collections of single isolates is satisfactory for many investigations of adaptation and evolution of P. aeruginosa to the CF airways.